Semiconducting properties of Cu2In3VO9 ceramic material. Issue 2 (1st February 2017) - Groń, T.; Bosacka, M.; Filipek, E.; Pacześna, A.; Urbanowicz, P.; Sawicki, B.; Duda, H.
Abstract: Cu2 In3 VO9 has been characterized by UV–vis–NIR and dielectric spectroscopy and measurements of its electrical conductivity and thermoelectric power to be a semiconductor with the activation energy E a1 =0.61 eV and E a2 =0.03 eV in the intrinsic and extrinsic region, respectively, the direct allowed energy gap E g =1.09 eV, the change of sign of the thermoelectric power from p to n at T n-p =400 K, the strongly temperature-dependent and frequency both dielectric constant ( ε r ) and loss tangent (tan  δ ) above 160 K. Moreover, the I - V characteristics and conductance provided the evidence of symmetrical and non-linear behaviour typical of strong emission of charge carriers induced by temperature and voltage. These results are interpreted in the framework of vacancy acceptor and donor levels in the honeycomb lattice structure forming a two-dimensional frustrated system assuming the relaxation process like with Maxwell-Wagner or Jonscher.